SYSTEM DESIGN PRICING GOODS AT PT HERNA MADIPA - Budiyono Soemadi; Ir Susi Wagiyati, MM (Jurnal Sistem Informasi, 1997)
With the increase of the total population from year to year, hence the need for goods or services to be especially important to both the needs of industry, agriculture, or the need for daily life. Variety of ways that the travel in fulfilling requirements the need to make producers always want to know how it should be done, so there were no matters that are not in want. Therefore, with the computerized system within a company can generate more accurate reports, saving time and providing convenience in the process of data search